Emotional Intelligence, Individual Work Performance And Job Involvement As Predictors Of Organizational Commitment Among Healthcare Professionals. - Ajay Kumar Dogra, Pooja Dogra (European Economic Letters (EEL), 2024)
The field of human resource management in healthcare sector is witnessing significant growth, as leaders and managers encounter multiple hurdles in their efforts to establish a highly effective and efficient organization. The commitment of employees is essential for achieving success. Psychological principles such as emotional intelligence and emotional labor have a substantial influence on results within the service industry. It is crucial to prioritize both mental and physical well-being in demanding healthcare environments. Organizations prioritize improving individual job performance, and emotional intelligence can aid in this by acknowledging, comprehending, and controlling one's own and others' emotions. A self-administered questionnaire was used to survey 120 healthcare personnel in three multi-specialty hospitals in Chandigarh Tricity, India. The survey comprised of demographic data, the Wong & Law Emotional Intelligence Scale (WLEIS), feedback on Individual Work Performance (IWP), and statements regarding organizational commitment. An accurate and trustworthy analysis of the data was conducted using Structural Equation Modelling (SEM) using SMART PLS. The study utilized a convenient sampling procedure to choose eligible individuals. The results were provided in the concluding part, emphasizing the significance of organizational commitment in the healthcare industry. The study validates the influence of emotional intelligence on job performance and organizational commitment, specifically within the healthcare industry. The statement proposes that senior executives should provide a transparent atmosphere to safeguard employees from organizational politics and promote emotional intelligence, resulting in improved job engagement and performance. The study additionally proposes that firms should offer ongoing training and current knowledge to enhance employees' emotional intelligence. The results can be utilized by individuals with a vested interest and decision-makers to formulate tactics to alleviate workplace politics and uphold elevated levels of emotional intelligence.